Systematic Literature Review: Mind Mapping Learning Model on Students' Creative Thinking Skills in Natural and Social Sciences Subjects in Elementary Schools - Apriani, Mela; Hidayah, Nurul; Ningrum, Ayu Reza (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
The purpose of the study was to analyze the application of the mind mapping learning model to students' creative thinking skills in natural and social science subjects in elementary schools. The research method used a systematic literature review with data sources collected through publish or perish indexed in the Google Scholar database between 2023 and 2025. Data analysis was carried out using descriptive analysis. The stages carried out in data analysis were (1) planning, (2) conducting, (3) reporting. The results of the study showed that out of a thousand articles that appeared, they were narrowed down to one hundred selected articles that were then in accordance with the application of the mind mapping learning model to students' creative thinking skills in natural science subjects in elementary schools, there were twenty-four articles. Based on the articles that have been analyzed, the application of the mind mapping learning model significantly improves students' creative thinking skills in natural and social science subjects in elementary schools. Analysis of the twenty-four articles reviewed indicates that this model not only helps students understand and remember information, but also encourages active involvement and collaboration in the learning process. So it can be concluded that the mind mapping model has proven effective in improving students' creative thinking skills, with a positive impact that can be felt in various educational contexts.